Cost-effectiveness analysis of a telemonitoring program on patients with heart failure in Normandy: an 8-year retrospective analysis (2009–2017). (25th November 2020) - Sabatier, R; Legallois, D; Jodar, M; Donio, V; Courouve, L; Hauchard, K; Boudevin, F; De Chalus, T; Belin, A; Milliez, P
Abstract: Background: SCAD is a 3-month telemonitoring program for HF patients, associated with therapeutic education, proposed after an acute HF episode. SCAD is based on an interactive algorithm allowing to generate educative messages and alarms based on patients' responses registered on a digital tablet. It is funded by the French Health Insurance through a pilot program: ETAPES (470€/patient). Purpose: To describe the profile of patients using SCAD & assess the medico-economic impact of the SCAD system. Methods: Multicenter retrospective cohort study using SCAD data matched with French Health Insurance data. All patients telemonitored by SCAD in 7 centers have been included, since 01/01/2010 to 12/31/2016. Only direct costs were considered, estimated from a societal perspective limited to reimbursements. Analyses were performed to assess the difference in healthcare consumptions and costs between the year before and the year after inclusion in the SCAD program. Patients who died in the 12 months after SCAD initiation were excluded. Results: 627 patients benefited from SCAD program between 01/01/2010 and 12/31/2016 and were retrieved in French Health Insurance data through probabilistic matching. Out of the 627 patients, 99 died in the 12 months after SCAD initiation. Analyses were performed on 528 patients.72.2% were male, mean age was 66.0 years old and mean BMI 28.2. HFrEF represented 51.9% of patients, HFmrEF 25.9% and HFpEF 22.2%. 58.0% were in NYHA class 2 at baseline, 29.2% in class 3, 8.5% in class 1 and 4.3% in class 4. Mean Charlson Comorbidity Index score was 2.6 at baseline. Patients reported their level of fatigue (10 representing significant fatigue) and morale (10 = good morale) at baseline: mean fatigue=4.0/10 & mean morale=7.4/10. Medico economic results are presented in table 1 and show an important & significant decrease of hospitalizations costs and some transfer of cost toward ambulatory care. Conclusion: On the year following remote monitoring, total health expenditure has been reduced by 18% on average (mean=3 210€/patient) and 42% in median (5 500€/patient) vs 12 months before. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): This analysis has been funded through an institutional grant from Amgen